Behavior of nursing students regarding the risks of accidents with sharps (Research, Society and Development, 2021)
The study aims to verify the behavior regarding the risks for accidents with sharps in undergraduate nursing students, from a public Higher Education Institution in the interior of Amazonas, Brazil. This research is quantitative, descriptive, cross-sectional, with the target audience of undergraduate nursing students at the Institute of Health and Biotechnology of the Federal University of Amazonas. The data collection was carried out by 2 previously trained interviewers, from July to August 2017. The sample consisted of 94 students, of which 62.8% were female, mean age 22.5 years , and 78.7% were single. It was found that the majority (89.7%) used Personal Protective Equipment in practical classes and the prevalence of 5 accidents with sharps. Additional research is suggested to investigate the actions taken in relation to accidents with sharps that reach this public.